IPGP laboratory data on granular flows extquotesingle high-frequency seismic signals - Matthew Iain Arran; Anne Mangeney; Julien de Rosny; Maxime Farin; Renaud Toussaint; Olivier Roche (PANGAEA, 2020)
Data from laboratory experiments in which glass beads flowed, via an opening of a given height h_g, into and through a channel at a given incline \tan \theta. Over the duration of each experiment, we recorded: 1) the mass outflow from the channel; 2) the voltage outputs of i) a force sensor and ii) accelerometers, fixed to an instrumented plate in the channel extquotesingles base; and 3) images of the flow, captured through the channel extquotesingles transparent side wall by a high-speed camera. The analysis of voltage outputs and high-speed camera images was calibrated by i) measuring the force sensor extquotesingles responses to a fixed vertical load, ii) examining the accelerometers extquotesingle responses to vertical impacts of individual glass beads, and iii) capturing images of a checked calibration pattern and of static beads. Data here comes from these calibration measurements, an experiment at h_g = 20 mm and \tan \theta = 0.44, and another at h_g = 28 mm and \tan \theta = 0.52. The full 340 GB of data, from three experimental repeats at each of 19 combinations of h_g and \tan \theta, will be available from the authors until at least 2025, care of Anne Mangeney.